FORAMINIFERS AND DEPOSITIONAL ENVIRONMENTS OF UPPER PALEOCENE SEDIMENTS IN THE NORTHEASTERN PERI-TETHYS - Stupin S.I. (My University, 2004)
In the northeastern Peri Tethys, the Goryachii Klyuch facies of the upper Paleocene are much more widespread than it was believed before. The facies correspond to dark colored, predominantly carbonate-free sediments bearing a specific foraminiferal assemblage with dominating agglutinated forms. These sediments accumulated in epicontinental basins, where the near-bottom water layer was likely contaminated by carbon dioxide that resulted in dissolution of calcareous foraminiferal tests.
Keywords: Paleocene; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен